2021
DOI: 10.3390/pathogens10111377
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 2: The Neglected Threat

Abstract: West Africa has the highest prevalence of human immunodeficiency virus (HIV)-2 infection in the world, but a high number of cases has been recognized in Europe, India, and the United States. The virus is less transmissible than HIV-1, with sexual contacts being the most frequent route of acquisition. In the absence of specific antiretroviral therapy, most HIV-2 carriers will develop AIDS. Although, it requires more time than HIV-1 infection, CD4+ T cell decline occurs more slowly in HIV-2 than in HIV-1 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 78 publications
(123 reference statements)
0
26
0
Order By: Relevance
“…Indeed, the number of new HIV diagnoses fell by more than 50% in the second and third years compared with the first year. Other groups have also acknowledged this challenge while addressing the number of new HIV‐positive cases detected in ED screenings [ 29 , 30 ]. All these observations strengthen the idea that screening opportunistically yields more diagnosis and better outcomes of earlier diagnosis than risk‐based testing alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the number of new HIV diagnoses fell by more than 50% in the second and third years compared with the first year. Other groups have also acknowledged this challenge while addressing the number of new HIV‐positive cases detected in ED screenings [ 29 , 30 ]. All these observations strengthen the idea that screening opportunistically yields more diagnosis and better outcomes of earlier diagnosis than risk‐based testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…Even though about two‐thirds of the patients screened were of Portuguese origin, over 60% of HIV cases were confirmed among people whose country of origin was not Portugal. Notably, 7.2% of infections were of HIV‐2, a finding associated with the historical presence of Portugal in African countries, namely Guinea‐Bissau, which has a high prevalence of HIV‐2 [ 30 , 31 ]. Previous studies have reported a higher burden of missed opportunities for HIV diagnosis among migrant populations in Europe, particularly those of African origin [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO-d 6 ) δ 9.86 (s, 1H, NH), 7.68 (dd, J = 8.7, 6.7 Hz, 1H, Ph-H), 7.57 (d, J = 9.0 Hz, 2H, Ph-H), 6.90 (d, J = 9.0 Hz, 2H, Ph-H), 6.65 (s, 2H, NH 2 ), 6.50 (dt, J = 11.9, 3.1 Hz, 1H, Ph-H), 6.38 (td, J = 8.6, 2. 6 2-Amino-4-bromo-N-(4-methoxyphenyl)benzamide (7d). White solid, yield: 69%.…”
Section: -((4-nitrophenyl)sulfonyl)piperazin-2-one (2)mentioning
confidence: 99%
“…HIV-2 is composed of nine groups termed A to I, of which group A is by far the most disseminated [ 4 , 5 ]. HIV-2 differs markedly from HIV-1 in the infection course, having a much longer asymptomatic phase, slower clinical progression and lower perinatal and sexual transmission rates (reviewed in [ 6 , 7 ]. In contrast to HIV-1-infected patients, plasma viral load is low or undetectable in most HIV-2-infected patients, irrespective of antiretroviral treatment [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%